Relative growth and morphological sexual maturity of the mangrove crab Aratus pisonii (H. Milne Edwards, 1837) (Decapoda, Brachyura, Sesarmidae) on the southern coast of the state of Sao Paulo, Brazil - Pescinelli, Regis Augusto [UNESP]; Davanso, Thiago Maia [UNESP]; Costa, Rogerio Caetano da [UNESP] (Taylor &francis Ltd, 2015)
Growth in crustaceans is characterized by ontogenetic differentiation during the development of their body structures, so studies on relative growth are widely applied in this group. In this study, the growth pattern of the body structures was verified through the analysis of relative growth, and then, morphological sexual maturity of the mangrove crab Aratus pisonii (H. Milne Edwards, 1837) was estimated. The carapace width (CW), cheliped propodus length (PL), cheliped propodus height (PH), propodus width (PW), abdomen width (AW), and first pleopod length (FPL) of the crabs were measured. The relationships that best showed changes in the allometric coefficient among demographic categories were FPL vs. CW for males and AW vs. CW for females. This study verified the increased size of the cheliped in terms of length, width, and height, which occurred mainly in adult males. This increase reflects the importance of this structure in the reproductive processes of A. pisonii. For females, the increase in abdomen growth reflects their reproductive potential, since it is a structure that provides protection for eggs.
Keywords: development; reproduction; allometry